Pengaruh Perbedaan Ayunan Pengelasan Dengan Metode SMAW Terhadap Kekuatan Tarik Pada Baja ST 37 Strip 5 MM - Ramadhan, Muhammad Hardiman Nur (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The purpose of this study was to see the effect of differences in welding swing on the tensile strength of 5 mm strip iron. The number of research samples was 6 pieces divided into two groups, the first group of 3 pieces welded with zig-zag welding swing, the second group of 3 pieces welded with spiral welding swing. The tensile test object used a tensile testing machine to determine the tensile stress value of the welding swing of each test object by slowly applying a load or force until the test object broke. This research method uses quantitative with a comparative experimental approach. The results of the welding tensile stress test of each test object sample welded with zig-zag and spiral welding swing joints showed that there was a similarity in the tensile test data, namely normal distribution, and similarity in variance. Hypothesis testing was obtained from the results of the tensile stress test of SMAW welding results with zig-zag and spiral welding swings showing a Tcount value of -8.021 (dk) = n1 + n2-2 at a significance level of 0.01 or 1%, a Ttable of 4.604 was obtained. So that the magnitude of the tensile stress of SMAW welding results with zig-zag and spiral welding swings has no significant influence.